2010
DOI: 10.1177/1420326x10389277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Airborne Total Volatile Organic Compounds of Niagara Falls Residences as Compared to Resident Lifestyle

Abstract: An indoor air study was conducted during the summers of 2007 and 2008 to determine the effect(s) of resident lifestyle on the concentrations and distributions of volatile organic compounds (VOCs) in residences of the city of Niagara Falls, New York. A GrayWolf Sensing Solutions Total Volatile Organic Compound (TVOC) detector was used to measure TVOC concentrations and generic air readings of five predetermined locations within each of 58 residences. Factors including smoking, asthma, furnace filter condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…For comparison, a recent study of TVOC concentrations in homes reported an average concentration of 337 ppb [13]. Only three of the salons in our study had concentrations less than this value.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…For comparison, a recent study of TVOC concentrations in homes reported an average concentration of 337 ppb [13]. Only three of the salons in our study had concentrations less than this value.…”
Section: Discussioncontrasting
confidence: 50%
“…The median salon averaged TVOC concentration in our study was 4,800 ppb, with a maximum level of 38,000 ppb. For comparison, a recent study of TVOC concentrations in homes reported an average concentration of 337 ppb [ 13 ]. Only three of the salons in our study had concentrations less than this value.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of all target VOCs had mean values of 115, 233, and 106 μg/m 3 in grocery, furniture/hardware, and apparel stores, respectively, in California, USA [12]; however, these concentrations only represented a fraction of the TVOC. For residential indoor air, a study reported an average (±SD) TVOC concentration of 327 (±119) ppb in 58 homes in Niagara Falls City, NY [34]. In 37 US schools, the total target VOC (TTVOC) concentration averaged 42 μg/m 3 with a maximum of 197 μg/m 3 [35].…”
Section: Discussionmentioning
confidence: 99%